TÜRKMENİSTAN YARGI SİSTEMİ - (:unkn) unknown (My University, 2016)
Bu çalışmada ülkemiz ile kültürel ve tarihsel ortak mirasa sahip Türkmenistan'ın yargı sistemi, Türkmenistan Anayasası ve ilgili kanun-kodeksler çerçevesinde incelenmiştir. Çalışmamızda yargı teşkilatı ve yargılamaya dahil olan kişiler, yargılamaya dair ilkeler ışığında analiz edilmiştir. Böylece ülkemiz ve Türkmenistan yargı sistemleri arasında bir mukayese imkanı da doğmuş olacaktır.

In this study, Turkmenistan's judicial system will be examined in the framework of the Turkmenistan Constitution and other related laws. Such that Turkmenistan has a common cultural and historical heritage with our country. In our study, issues about judicial organization and persons who involved in the judgement will be analyzed in the light of the principles concerning to judgement. By this way, the possibility of a comparison between the judicial systems of Turkey and Turkmenistan will be emerged.
Turkmenistan's Judicial System
Keywords: Hukuk